THE EFFECT OF INTRADIALYSIS STRETCHING EXERCISE ON THE SCALE OF RESTLESS LEG SYNDROME - Nur, Ahyar; Erika, Kadek Ayu; Sinrang, Andi Wardihan (Journal of Islamic Nursing, 2018)
Restless legs syndrome (RLS) is a common sensorimotor disorder in patients with chronic renal failure who undergo hemodialysis (HD). Pharmacological therapy is the main choice of RLS treatment that is at risk of side effects. Physical optimization of HD patients through stretching exercise is considered potentially effective in treating restless legs syndrome. This study aimed to identify the effect of stretching exercise on RLS in patients with chronic renal failure who underwent HD at Hasanuddin University Hospital. This research method used quasi experiment with pre- and post-test with control group design. The subjects in this study were 20 HD patients divided into two groups: 10 patients, Intervention and 10 control patients. Stretching exercise is given twice a week during the hemodialysis process, for 4 weeks. The RLS scale is measured using IRLS Scale. The collected data were then analyzed using the Wilcoxon test. The results showed that the respondents who received stretching exercise intervention experienced a decreaseof the RLS scale more significantly than the control group with ρ = 0.001 (ρ